Clinical outcome before and after COVID-19 quarantine in patients affect of knee and hip osteoarthritis: Experience of orthopedic department in one of the first European country involved in COVID-19 pandemic. - Larghi, Marco Mattia; Grassi, Miriam; Luca, Faugno; Placenza, Emanuele; Rampulla, Corrado; Manzotti, Alfonso (Acta Biomedica Atenei Parmensis, 2020)
Background: The emergency caused by COVID-19 Pandemia has resulted in a complete suspension and consequent delay of common planned surgery such total hip replacement in patients affect by osteoarthritis. At the same time, the issue of the quarantine imposed changes to the normal lifestyle of these patients. The purpose of our study is to evaluate how the presence of these two factors affect the quality of live of patients living in the Italian red zone.Methods: From outpatient pre-operative assessment we collect data about: demographic data, WOMAC score, NRS (Numeric rating scale 0-10), PCS SF12 and MCS SF12 score. Selected patients were therefore contacted by telephone call and re-assess using the same score. In addition, patients were asked if they intended to undergo the planned surgery again despite the current emergencyResults: 14 patient have been recruited for the study. Male/female ration was 10/4, mean age was 70 years. Pre operative outpatient assessment mean WOMAC score was 44,86 (SD ± 8,52) , mean NRS was 8,07 (SD ± 1,33), PCS SF12 was  30,33 (SD ± 5,0) and MCS SF12 was 40,95 (SD ± 3,51).  At re-evalutation the mean WOMAC score was 32,86 (SD ± 17,88) , mean NRS was 5,79 (SD ± 3,66), PCS SF12 was  39,9 (SD ± 3,70) and MCS SF12 was 50,14 (SD ± 6,86)Conclusion: The exceptionale pandemic from Covid-19 has profoundly changed our lifestyle, impacting normal daily activities but also on regular surgical activity in patients affected by osteoarthritis. Our study suggested that the lifestyle changes imposed by the situation led to an improvement of clinical score. This shows how an exceptional event can affect many aspects of daily life.